LOCAL GOVERNMENT DISCRETION AND ACCOUNTABILITY IN TURKEY - GÜNER, AYŞE (WILEY-BLACKWELL, 2013)
After ratification of the European Charter of Local Self-Government in 1993, Turkey has witnessed major local government reform efforts in 2000s. The policy objectives of these reforms were granting more political, administrative and fiscal discretion to local governments along the principles of democratic decentralization and strengthening accountability linkages between citizens and local governments. We employ a diagnostic framework to analyse the impact of these reforms. We argue that reforms have achieved limited success in improving decision-making autonomy and accountability of local governments. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: decentralization; local governance; accountability; Turkey; DECENTRALIZATION